Effects of Non-Spatial Pre-Training on Learning and Memory Impairment Detection in the Morris Water Maze - KOOMHIN, Phanit; SATTAYAKHOM, Apsorn; PALIPOCH, Sarawoot; PUNSAWAD, Chuchard; TAPECHUM, Sompol (Walailak Journal of Science and Technology (WJST), 2016)
One of the most popular learning and memory tests is the Morris water maze. The Morris water maze is a circular pool filled with water with a hidden platform under the water surface. The test is appropriate for rodents, especially rats and mice. The testing protocol comprises 2 parts that evaluate learning ability and memory retention. When animals are placed in the pool, they experience stress, which is the driving force for discovery of a strategy to leave the water. In the experiment, animals use environmental cues to find the location of the hidden platform in the pool. After consecutive training days, animals can more quickly locate the hidden platform. The last day of the task involves a memory test without the platform. It shows a limitation of the test in mild learning and memory deficit models such as 2-vessel occlusion. Differences between the normal and memory impairment models are expressed only in a narrow range. So, we tried to modify the original protocol for mild learning and memory impairment models. We used an albino rat strain for the experiment. A pre-training strategy of 3 days of swimming in the pool with a visible platform prior to the ordinary task was used. The results suggest that this pre-training strategy improved learning and memory in the rat model. When compared to normal rats and 2-vessel occlusion rats (a rat model for vascular dementia), those that participated in the pre-training strategy showed an increase in the percent difference of area under the curve for learning trials. In conclusion, the pre-training strategy increases ability to discriminate learning and memory impairment in the rat model, especially for the mild learning and memory deficit models.